Additive, modular functionalization of reactive self-assembled monolayers: toward the fabrication of multilevel optical storage media1. Issue 16 (28th April 2015) - Gentili, Denis; Barbalinardo, Marianna; Manet, Ilse; Durso, Margherita; Brucale, Marco; Mezzi, Alessio; Melucci, Manuela; Cavallini, Massimiliano
<x xml:space="preserve">Abstract</x> We fabricated a multi-level fluorescent tag, consisting of two overlapping micrometric logic patterns of two fluorescent SAMs where each molecule preserves the individual functional properties.